Pattern evolution of antidepressants and benzodiazepines use in a cohort - Geisy de Carvalho Alcantara; Evandro Silva Freire Coutinho; Eduardo Faerstein (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE In recent decades there has been an increase in the use of antidepressants (AD) and a decrease in the use of benzodiazepines (BDZ). Prevalence, cumulative incidence, and factors associated with the incidence of AD and BDZ use in a Brazilian population were estimated in this article. METHODS Data were collected with a self-administered questionnaire in a cohort of employees from a university in Rio de Janeiro. The prevalence of the use of AD and BDZ was calculated for 1999 (4,030), 2001 (3,574), 2006-07 (3,058), and 2012 (2,933). The cumulative incidences of the use of AD and BDZ between 1999 and 2007 were estimated by the Poisson models with robust variance estimates. RESULTS In 1999, the prevalence of the use of AD and BDZ were 1.4% (95%CI: 1.1-1.8) and 4.7% (95%CI: 4.1-5.4), respectively; in 2012, they were 5.4% (95%CI: 5.5-6.2) and 6.8% (95%CI: 6.0-7.8). The incidence of use, between 1999 and 2007, was 4.9% (95%CI: 4.2-5.7) for AD and 8.3% (95%CI: 7.3-9.3) for BDZ. The incidences of AD and BDZ use were higher among women and participants with a positive General Health Questionnaire. CONCLUSION In this population, the increase in the use of AD was not accompanied by a decrease in the use of BDZ, showing the prescriptions for psychotropic medication do not follow the currently recommended guidelines for treatment of common mental health disorders.